Flawed external validation study of the ADNEX model to diagnose ovarian cancer. - Van Calster, B; Steyerberg, E; Bourne, T; Timmerman, D; Collins, G; TG6 of the STRATOS initiative, (Elsevier, 2016)
External validation studies of prediction models are of utmost importance in order to assess the performance a prediction model in different locations. We therefore read with interest the recent external validation study of the ADNEX model 1 For patients with a persistent adnexal tumor who underwent surgery, the ADNEX model predicts the risk of five tumor types: benign, borderline malignant, stage I cancer, stage II-IV cancer, or secondary metastatic cancer. The model was developed on data from 5909 patients collected at 24 centers, in 10 countries, between 1999 and 2012. ADNEX aims to assist clinicians in making appropriate clinical decisions for patients presenting with an adnexal mass. For the ADNEX model, it is natural to first evaluate the prediction of malignancy, followed by an evaluation of the multiclass prediction of malignancy subtypes, similar to other multiclass validation studies [4]. This approach is followed in the recent paper, but there are a number of important issues around the design, analysis, and reporting we wish to raise.